The Role of Wearable Technology in Enhancing Physical Activity and Supporting Health Status Improvement: A Systematic Literature Review - Rohman Daka; Aprilia Rambe (Journal of Health, Medical, and Psychological Studies, 2026)
Physical activity plays a crucial role in maintaining health and preventing non-communicable diseases; however, participation levels remain insufficient across different populations. The development of digital health technologies, particularly wearable devices such as fitness trackers and smartwatches, offers innovative solutions for monitoring and promoting physical activity. This study aimed to examine the role of wearable technology in enhancing physical activity and supporting health status improvement through a systematic literature review based on the PRISMA 2020 guidelines. Literature searches were conducted in PubMed, Scopus, ScienceDirect, MEDLINE, and ProQuest for studies published between 2016 and 2026. Following duplicate removal, screening, and eligibility assessment using the PICO framework, 22 articles from 5,747 identified records were included in the final synthesis. The findings demonstrate that wearable technology enables objective monitoring of physical activity through indicators such as step count, activity intensity, duration, and heart rate. The reviewed studies reported improvements in physical activity awareness, motivation, self-monitoring, and health-related behaviors across children, adolescents, adults, and older adults. Wearable interventions combined with goal setting, personalized feedback, and behavioral support showed more consistent outcomes than device use alone. Wearable technology represents a promising strategy for promoting active lifestyles and improving population health outcomes.